Employment type and policy compliance with strict measures during public health crises: evidence from self-employed workers in China - Lyu, Tongzhou; Yan, Ruyi; Zhao, Yongxin; Wang, Jiangyin; Zhang, Xuke; Hong, Zhen; Huang, Xiaozhu (Frontiers in Public Health, 2025)
BackgroundThe rapid rise of non-standard types of employment—particularly self-employment—has significantly reshaped labor market structures and public policy systems. Compared to employees, self-employed individuals often lack long-term formal labor contracts and experience substantial income volatility, making them especially vulnerable. These vulnerabilities are further exacerbated during public health crises, adding complexity and uncertainty to policy implementation. This study examines the policy compliance of self-employed workers under strict public health measures, with the aim of exploring the relationship between employment type and policy compliance.MethodThis study draws on 2,325 valid responses from the 2021 Chinese General Social Survey (CGSS2021). An Ordinary Least Squares (OLS) regression model is employed to compare levels of policy compliance between self-employed individuals and employees under strict public health measures. The analysis further examines how structural differences associated with employment type influence compliance behavior.ResultsSelf-employed individuals demonstrate significantly higher levels of policy compliance than employees during public health crises, with results statistically significant at the 1% level. Heterogeneity analysis further indicates that low-income self-employed individuals exhibit even greater compliance, also significant at the 1% level. In addition, self-employed workers in digitally advanced regions show higher compliance compared to their counterparts in less developed areas, with this difference likewise significant at the 1% level.ConclusionEmployment type is closely associated with policy compliance during public health crises. Challenging the common view that self-employed individuals are less compliant due to weak institutional constraints, this study finds they are more willing to comply. Motivation theory helps explain this pattern: normative pressures and external cues may heighten their sense of responsibility, driving normative compliance. While income instability, limited social protection, and regulatory uncertainty amplify risk awareness, driving calculative compliance. Heterogeneity analysis indicates that low-income self-employed individuals, driven by heightened risk perception and limited resilience, are more likely to comply with policies. Those in digitally advanced regions also exhibit higher compliance, possibly due to more efficient access to information, stronger industry governance, and more effective government oversight. This study contributes to a theoretical understanding of how employment type influences policy behavior, highlighting the distinct constraints and motivational foundations for policy implementation.